Impact of the Covid-19 pandemic and lockdowns on the education and mental health of physiotherapy students in France: a descriptive cross-sectional study with national online survey - Arnaud Delafontaine; Gabriel Saiydoun; Maxime Vallée; Laurent Fabeck; François-Régis Sarhan; Thomas Rulleau; Sylvain Gautier; Nicolas Pinsault (Medical Journals Sweden, 2024)
Objective: To determine the impact of the SARS-CoV-2 (COVID-19) pandemic and lockdowns on the mental health status, training, perceptions of the physiotherapy profession, and career plans of French physiotherapy students. Design: A descriptive cross-sectional study was conducted, representing the first and only survey of its kind, using a national online survey. Subjects: A total of 2678 French physiotherapy students participated in the study. Methods: Mental health status was assessed using the validated French versions of established depression, anxiety, and insomnia scales. Results: The survey revealed that female sex, age below 21 years, living alone, and having a psychiatric history or COVID-19 risk factors were associated with more severe symptoms of depression, anxiety, and insomnia in the surveyed students. In addition, stress, anxiety, and depression induced by the COVID-19 crisis were linked to apprehension about continuing practical training in physiotherapy. These factors also affected students' perceptions of the profession and the initially envisioned mode of practice, particularly among fifth-year students (odds ratio (OR) = 2.25, 95% confidence interval (95% CI) = (1.69, 2.99), p < 0.001). Notably, the pandemic significantly reduced the desire of these students to pursue a career as physiotherapists (adjusted OR (aOR) 1.41 (1.06, 1.86)). Conclusion: French physiotherapy students, especially those in their fifth year, have experienced significant impacts from the COVID-19 pandemic, affecting their mental health, education, perceptions of the physiotherapy profession, and career plans.